Beyond access: Gender- transformative financial inclusion in agriculture and entrepreneurship - Njuki, Jemimah; Melesse, Martha; Ng'weno, Amolo; Rappoldt, Anne; Phelane, Comfort; d'Anjou, Jesse; Hassan, Michelle; Ketley, Richard; Vossenberg, Saskia (International Food Policy Research Institute, 2019)
Acore tenet underpinning financial inclusion is the notion that everyone has access to and usage of affordable financial products and services that meet their needs—whether those are savings, credit, insurance, or transactions or any combination of such services. Fulfilling this aspiration rests on a number of assumptions: that people need a range of financial products and services to fulfill their diverse daily activities; that such services will be worth using only if they are delivered with sufficient quality, including convenience and affordability, that everyone can safely use them; and that a well-functioning marketplace exists within which multiple competing providers operate in an enabling framework set through effective regulation. An increasingly central aspect of the financial inclusion vision involves the financial literacy and capability of the customers, who must have the knowledge, skills, and behaviors that enable them to make sound financial decisions.